Dark road home - Ludwig, Elizabeth (Ludwig, Elizabeth. Edge of freedom, 2013)
"Hunted by dangerous enemies and betrayed by those they loved, can Ana and Eoghan, 19th century Irish immigrants in New York, forgive the wounds of the past and learn to trust again?"--Provided by publisher.